The moderating effect of transformational leadership on the relationship between individual and organizational factors and deviant workplace behaviour - Javed, Iqbal (2019)
This thesis aims to empirically examine the moderating role of transformational leadership in defining the impact of individual and organizational factors on deviant workplace behaviour. Deviant workplace behaviour is arguably one of the most vital areas of research. Previous literatures indicate that there is a connection between the impact of employee’s behaviour and the performance of public organizations. Hence, this explanatory research reviews existing literatures on transformational leadership, individual and organizational factors, and deviant workplace behaviour from different methodological strands. Through this approach, its findings are subsequently synthesized to formulate a new theoretical framework which is supported by other theories, including social exchange theory, social learning theory and psychological breach contract theory. Hypotheses are developed to test the relationship among the variables used in this study. For the purpose of data collection, a self-administered questionnaire is used to collect data from 380 individual employees of 20 public organizations in the Punjab province of Pakistan. SPSS-21 and Smart PLS.3 packages are employed to analyze the acquired quantitative data. To test the hypotheses, partial least squares method of structural equation modeling (PLS-SEM) is adopted. Results from PLS-SEM reveal a significant relationship of the direct impact of individual and organizational factors on deviant workplace behaviour in the public organizations in Punjab. Nonetheless, the findings indicate that the moderated effect of transformational leadership on deviant workplace behaviour is not fully consistent with the hypothesis. When compared to the correlation of dark triad personality traits and deviant workplace behaviour, the findings show a weaker relationship between the individual factor, notably big five personality traits and the deviant workplace behaviour. In sum, the analysis of the findings supports the view that transformational leadership can override predispositions of individuals to engage in deviant workplace behaviour. This research is significant in enriching the body of knowledge in the existing literature, particularly transformational leadership, individual and organizational factors and deviant workplace behaviour. In terms of its practical contribution, this study could serve as a guideline for leaders and office bearers of Pakistani public organizations to develop effective mechanism in overcoming the prevalent incidents of deviant workplace behavior in the country.